Using Narrative Medicine to Teach Spiritual Care Competence Among Health Professions Students - Chia-Chen Chang; Jaw-Shiun Tsai (American Journal of Hospice and Palliative Medicine®, 2026)
Background Spiritual care is an important component of whole-person care, but formal training remains limited in many health professions curricula. This study examined changes in spiritual care competence following a 16-week narrative medicine course among students from medicine, psychology, public health, and health management programmes in Taiwan. Methods A quasi-experimental pretest and posttest design compared students who enrolled in the course (n = 14) with those who did not (n = 16). Participants completed a four-domain Spiritual Care Competency Scale before and after the course. Students in the intervention group also provided written reflections as part of the course evaluation. Results Twenty-six students completed both assessments. The intervention group showed significantly greater gain scores than the comparison group in intrapersonal spirituality, spiritual care assessment and planning, and spiritual care intervention and evaluation. Gain scores for interpersonal spirituality did not differ significantly between groups. Course reflections provided supplementary information on students’ perceived learning experiences. Conclusions Participation in the narrative medicine course was associated with improvements in selected dimensions of spiritual care competence. Narrative medicine may be useful for integrating reflective learning into spiritual care education.